The impact of teaching status on trauma center clinical outcomes in the United States. Issue 34 (August 2019) - Elkbuli, Adel; Dowd, Brianna; Flores, Rudy; Boneva, Dessy; McKenney, Mark
Abstract : Abstract: Teaching status/academic ranking may play a role in the variations in trauma center (TC) outcomes. Our study aimed to determine the relationship between TC teaching status and injury-adjusted, all-cause mortality in a national sampling. Retrospective review of the National Sample Program (NSP) from the National Trauma Data bank (NTDB). TCs were categorized based on teaching status. Adjusted mortality was determined by observed/expected (O/E) mortality ratios, derived using TRauma Injury Severity Score methodology from the Injury Severity Score and Revised Trauma Score. Chi-square and t test analyses were utilized with a statistical significance defined as P <.05. Of the 94 TCs in the NSP, 46 were university, 38 were community teaching, and 10 were community nonteaching. For the University TCs, 62.8% were American College of Surgeons (ACS) level 1 and 81.2% state level 1. Of the community teaching TCs, 39.0% was ACS level 1 and 35.1% was state level 1. Of the community nonteaching TCs, 0% was ACS level 1 and 11.1% was state level 1. University TCs had a significantly higher O/E mortality rate than community teaching (0.75 vs 0.71; P = .04). There were no differences in O/E between community teaching and nonteaching TCs (0.71 vs 0.70; P = .70). Community teaching and nonteaching TCs have lower injury-adjusted, all-cause mortality rates than University Centers. Future studies should further investigate key differences between University TCs and community teaching TC to evaluate possible quality and performance improvement measures.